ANALISIS PERAN KIP KULIAH DALAM HUMAN CAPITAL INVESTMENT DAN PEMERATAAN PENDIDIKAN TINGGI DI KABUPATEN BERAU: Studi Kualitatif Pada Mahasiswa Universitas Muhammadiyah Berau - MERLIN D (ECO-BUILD, 2026)
Higher education plays a strategic role in human capital development, yet access remains constrained by economic inequality, particularly among low-income families in peripheral regions such as Berau Regency. The Indonesia Smart College Card (KIP Kuliah) program was introduced by the Indonesian government to expand access to higher education for economically disadvantaged students with strong academic potential. This study aims to analyze the role of the KIP Kuliah program in human capital investment and the equalization of higher education access in Berau Regency, focusing on students of the Development Economics Study Program at Universitas Muhammadiyah Berau. A qualitative case study approach was employed, with data collected through in-depth interviews with eight KIP Kuliah recipients and one supporting informant, complemented by participatory observation and documentation, then analyzed using the Miles and Huberman interactive model supported by source and technique triangulation. The findings show that most recipients come from low-income families and highly depend on KIP Kuliah to pursue higher education. The program serves as an enabling factor that opens access to higher education, supports student retention through tuition fee waivers and living allowances, improves students' economic well-being through more structured financial management, and enhances motivation and psychological security as part of human capital development. However, challenges remain, including delays in fund disbursement, a mismatch between the living allowance and actual regional living costs, and the need for stricter recipient verification. The study recommends periodic adjustment of living allowances to regional cost-of-living indices, strengthening of academic mentoring, and improved financial literacy among recipients to optimize the program's long-term contribution to human capital development and educational equity.